2022
DOI: 10.1093/bjs/znac095
|View full text |Cite
|
Sign up to set email alerts
|

Core outcome set for symptomatic uncomplicated gallstone disease

Abstract: Background Heterogeneity of outcomes is a problem for assessing intervention effectiveness when considering treatments for uncomplicated symptomatic gallstone disease. The value to all stakeholders of outcomes that have been measured and reported to date is also unclear. The aim of this study was to develop a core outcome set for symptomatic uncomplicated gallstone disease. Methods An in person-meeting was held with patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The two patient and public involvement (PPI) partners (one grant holder/member of the project management group, and one independent member of the trial steering committee) were actively involved in discussions of the study results with the trial steering committee and the trial investigators, and they contributed to preparing the plain English summary. The PPI group (which was initially established as a focus group for the Core Outcome Set 38 but remained actively involved in the wider C-GALL project) was actively involved in discussions of the study results with the PPI partners and contributed to reviewing the plain English summary. At the conclusion of the study, the PPI partners reflected on their input and made suggestions for future research.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…The two patient and public involvement (PPI) partners (one grant holder/member of the project management group, and one independent member of the trial steering committee) were actively involved in discussions of the study results with the trial steering committee and the trial investigators, and they contributed to preparing the plain English summary. The PPI group (which was initially established as a focus group for the Core Outcome Set 38 but remained actively involved in the wider C-GALL project) was actively involved in discussions of the study results with the PPI partners and contributed to reviewing the plain English summary. At the conclusion of the study, the PPI partners reflected on their input and made suggestions for future research.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…Globally, gallstone prevalence affects approximately 10-20% of adults, imposing considerable economic burdens on individuals and societies (1)(2)(3)(4). Approximately 80% of gallstone patients remain asymptomatic; however, without timely intervention, the clinical course of gallstones can progress from asymptomatic carriers to symptomatic and complex conditions such as acute cholecystitis, cholangitis, pancreatitis, and, in rare instances, intestinal obstruction (5,6). Numerous studies have demonstrated that disorders of cholesterol metabolism, unhealthy lifestyle habits, genetic factors, obesity, and pregnancy significantly contribute to the development of gallstone disease (1,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Gallstones are formed in the gallbladder or bile ducts mainly due to unusually high cholesterol or bilirubin levels in the bile. About 80% of people with gallstones are asymptomatic, and about 20% will experience pain and complications related to gallstones [ 3 ]. In addition, if asymptomatic people do not receive timely intervention, asymptomatic people with gallstones will develop more complex diseases such as acute cholecystitis, cholangitis, and pancreatitis, which seriously affect the quality of life [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%